2020
DOI: 10.3390/diagnostics11010023
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic Diagnosis of Placenta Accreta Spectrum (PAS) Disorder: Ideation of an Ultrasonographic Score and Correlation with Surgical and Neonatal Outcomes

Abstract: The objective of this study was to evaluate a novel ultrasonographic scoring system for the diagnosis of PAS and the prediction of maternal and neonatal outcomes. In this retrospective study, 138 patients with at least one previous caesarean section (CS) and placenta previa were included. They were divided into four groups ranging from Group 0 (Non PAS) to Group 3 (Placenta Percreta) according to the histological or surgical confirmation. Their ultrasound examinations during pregnancy were reviewed according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…Previous studies have found that blood loss of more than 2500 mL was significantly associated with the need for blood transfusion, ICU admission, and other complications associated with bleeding such as acute renal failure or even maternal death [11,[13][14][15]. Antenatal detection of PAS disorders plays an important role in reducing hemorrhagic morbidities [16][17][18][19][20]. Two-dimensional (2D) ultrasonography is the recommended tool for the diagnosis of PAS, as it has a proven high detection rate and is available in most centers [7,11,13,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that blood loss of more than 2500 mL was significantly associated with the need for blood transfusion, ICU admission, and other complications associated with bleeding such as acute renal failure or even maternal death [11,[13][14][15]. Antenatal detection of PAS disorders plays an important role in reducing hemorrhagic morbidities [16][17][18][19][20]. Two-dimensional (2D) ultrasonography is the recommended tool for the diagnosis of PAS, as it has a proven high detection rate and is available in most centers [7,11,13,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…For US images, the diagnosis was made using an ultrasound score developed by our working group [ 21 ], previously described and based on ultrasound descriptors suggested by the European Working Group on Abnormally Invasive Placenta (EW-AIP), stratified by severity score and combined with anamnestic data ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Placenta accreta spectrum (PAS) disorders, previously defined as abnormally adherent placenta, define a variety of conditions characterized by abnormal adhesion and/or invasion of the placental trophoblast to the uterine myometrium. 1 The pathophysiologic mechanisms of PAS remain incompletely clarified. Still, its clinical sequel are clear: placental invasion and the associated hypervascularity involving the uterus and placenta which put women at a great risk for exposure to caesarean hysterectomy, massive hemorrhage, disseminated intravascular coagulopathy, and in the most catastrophic cases, death.…”
Section: Introductionmentioning
confidence: 99%